The association between hair cortisol and burnout is moderated by age, psychosocial, and immunological markers - Patrick D. Gajewski; Peter Bröde; Maren Claus; Klaus Golka; Jan G. Hengstler; Carsten Watzl; Edmund Wascher; Stephan Getzmann (Brain, Behavior, & Immunity - Health)
Background: Exhaustion and depersonalization are the core symptoms of the occupational burnout. However, burnout is not an all-or-nothing phenomenon, but can occur in a milder to moderate form in otherwise healthy employees. In the last two decades hair cortisol concentrations (HCC) were increasingly related to the cumulative effect of psychosocial stress at work. We analyzed data of the Dortmund Vital Study (Clinicaltrials.gov: NCT05155397) to explore the relationship of HCC and burnout symptoms. Moreover, we asked whether the HCC – burnout association was moderated by work ability, chronic stress, neuroticism, depressive symptoms, and stress-related immunological biomarkers such as T cell concentration, CD4/CD8 cell ratio, and proinflammatory cytokines TNF- α, IL-6, and IL-18. Methods: Burnout was assessed by the Oldenburg Burnout Inventory (OLBI), and the Maslach Burnout Inventory (MBI-D) in 196 working adults aged between 20 and 65 years (mean age 42.2 years). Several self-reported variables and biomarkers were collected. Results: The results showed an association between HCC and the burnout measures. A series of moderator analyses revealed that the association between HCC and burnout symptoms was substantial for low work ability, high chronic stress level, high neuroticism level, and mild to moderate depressive symptoms. Immunological markers moderated the HCC – burnout association for high concentrations of T cells, low CD4/CD8 ratio and low IL-6, IL-18 and TNF-α concentrations. These interactions were moderated by age showing the largest impact in middle-aged to older individuals. Conclusions: The present findings shed light on the complex interaction between burnout symptoms and work ability, chronic stress, personality, and the endocrinological and immunological responses across the working lifespan. These parameters should be considered when assessing the risk for developing burnout and validating the diagnosis of burnout. Trial registration: ClinicalTrials.gov NCT05155397; https://clinicaltrials.gov/ct2/show/NCT05155397.